2019
DOI: 10.1016/j.celrep.2019.04.111
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Ligases cIAP1 and cIAP2 Limit Cell Death to Prevent Inflammation

Abstract: Highlights d Acute cIAP1/2 deficiency in adult mice unleashes apoptosis and inflammation d cIAP1/2 limit inflammation by suppressing the activation of caspase-8 d cIAP1/2 also prevent embryonic lethality by limiting caspase-8-dependent cell death

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 77 publications
(100 reference statements)
4
45
0
Order By: Relevance
“…The specific polyubiquitination pattern on RIP1 that keeps it in complex I for proper downstream activation of NF-κB and MAPKs is fine-tuned by the activation of E3 ligases, such as c-IAP1/2 ( Bertrand et al, 2008 ; Mahoney et al, 2008 ; Varfolomeev et al, 2008 ; Silke and Vucic, 2014 ). The combined deletion of c-IAP1 and c-IAP2 in mice results in embryonic lethality and severe liver and intestinal damage in the adulthood, which can be rescued by TNFR1 knock-out or by TNF blockade, further emphasizing the functional and genetic relationship between these E3 ligases and TNF signaling ( Moulin et al, 2012 ; Zhang J. et al, 2019 ). However, these complexes are also governed through negative regulation by deubiquitinases (DUBs).…”
Section: Activation Of Nf-κb and Mapk Signaling By Tnfmentioning
confidence: 99%
See 2 more Smart Citations
“…The specific polyubiquitination pattern on RIP1 that keeps it in complex I for proper downstream activation of NF-κB and MAPKs is fine-tuned by the activation of E3 ligases, such as c-IAP1/2 ( Bertrand et al, 2008 ; Mahoney et al, 2008 ; Varfolomeev et al, 2008 ; Silke and Vucic, 2014 ). The combined deletion of c-IAP1 and c-IAP2 in mice results in embryonic lethality and severe liver and intestinal damage in the adulthood, which can be rescued by TNFR1 knock-out or by TNF blockade, further emphasizing the functional and genetic relationship between these E3 ligases and TNF signaling ( Moulin et al, 2012 ; Zhang J. et al, 2019 ). However, these complexes are also governed through negative regulation by deubiquitinases (DUBs).…”
Section: Activation Of Nf-κb and Mapk Signaling By Tnfmentioning
confidence: 99%
“…Inducible inactivation of OTULIN’s DUB function in adult mice results in extensive hepatocyte and intestinal crypt cell death, and inflammation, primarily driven by myeloid cells, in the heart and liver ( Heger et al, 2018 ). Similarly, co-deletion of Birc2 and Birc3 , which encode c-IAP1 and c-IAP2, respectively, in adult mice results in extensive hepatocyte death and crypt degeneration with intestinal villous atrophy and secondary inflammation ( Zhang J. et al, 2019 ). In both OTULIN and c-IAP1/2 deficient mice, cell death in the liver and intestines was associated with extensive cleaved caspase-3 immunolabeling, suggesting a predominance of apoptosis ( Heger et al, 2018 ; Zhang J. et al, 2019 ).…”
Section: Deciphering Tnf Signaling Regulation Through Genetic Mouse Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant caspase‐8 activity has been implicated in a variety of inflammatory diseases and, in some cases, can even drive lethality. For example, caspase‐8 drives lethal dermatitis in the absence of linear ubiquitin chain assembly complex (LUBAC; Taraborrelli et al , ), and caspase‐8 activity triggers embryonic lethality observed in Birc2 −/− Birc3 −/− mice (Zhang et al , ). Furthermore, caspase‐8‐dependent intestinal damage is a key driver for septic shock in mice (Mandal et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The observed downregulation of the IAP family and RIP1 in the Pd(T4) model exhibits the temporal nature of PDT-elicited activity. CIAP 1/2 is known to act as a ubiquitin ligase inhibiting RIP1 through proteosomal degradation [66]. This activity seems to happen before the IAP family is complexed with Smac [67], following its release from the mitochondria via MOMP induced by PDI and Bax.…”
Section: Discussionmentioning
confidence: 99%